Pembelajaran Pendidikan Pancasila: Penentuan Tema Karya Seni Siswa SMK Negeri 3 Kasihan Bantul - Dian Lestari; Heri Kurnia; Paiman (Prodi PPKn FKIP Universitas Pamulang, 2025)
The background of this research is because the researcher is interested in learning Pancasila Education towards determining the theme of students' artworks. This research aims to 1). Knowing the influence of (X1) on (Y) at SMK Negeri 3 Kasihan Bantul. 2). Knowing the influence of (X2) on (Y) at SMK Negeri 3 Kasihan Bantul. 3). Knowing the influence of (X3) on (Y) at SMK Negeri 3 Kasihan Bantul. 4). Knowing the influence of (X4) on (Y) at SMK Negeri 3 Kasihan Bantul. 5). Knowing the influence of X1, X2, X3, X4 simultaneously on (Y) at SMK Negeri 3 Kasihan Bantul. This research method uses quantitative research methods. The population of this study is all students of SMK Negeri 3 Kasihan Bantul with a total of 1,038 students using Simple Random Sampling with the provision that based on the Harry King nomogram table, if the total population is 1038 students, then the sample that can be taken with an error rate of 5% is as many as 265 students. The data analysis technique used to test the hypothesis is multiple linear regression. The results show 1). There was a significant influence (X1) on (Y) at SMK Negeri 3 Kasihan Bantul with a sig of 0.020 with a regression equation of 0.180. 2). There was a significant influence (X2) on (Y) at SMK Negeri 3 Kasihan Bantul with a sig of 0.000 with a regression equation of -302. 3). There was a significant influence (X3) on (Y) at SMK Negeri 3 Kasihan Bantul with a sig of 0.000 with a regression equation of 0.496. 4). There was a significant influence (X4) on (Y) at SMK Negeri 3 Kasihan Bantul with a sig of 0.000 with a regression equation of -604. 5). There was a significant influence of X1, X2, X3 and X4 simultaneously on Y at SMK Negeri 3 Kasihan Bantul with a sig of 0.000 ≤ 0.05 and Fcalculated 53,707 > Ftable 2,250. The magnitude of the determination coefficient (adjusted R2) of = 0.777 means that the independent variable simultaneously affects the bound variable by 77.7%, the remaining 22.3% is influenced by other variables that are not included in this study.